(untitled) (Przegląd Religioznawczy – The Religious Studies Review, 2023)
The article discusses important religious motifs that appear in the broad philosophical and artistic work of Miguel de Unamuno, Del sentimiento trágico de la vida en los hombres y en los pueblos. One of them is the problem of immortality, which is one of the most important issues that often appears in the reflections of the Spanish writer. The author distinguishes several levels of immortality: (1) biological, (2) cultural, and (3) species. Unamuno, using the Catholic tradition, navigates various dogmas of Catholic beliefs, while maintaining creative independence in these intellectual explorations. He also changed his mind towards the Catholic Church itself, believing that it limited the field of freedom in philosophical and religious discussions. However, in his late essays, Unamuno defended Christian culture as important for Spanish and European identity. With some reservations, the author’s philosophy of religion and culture can be classified as adequate to irrationalism and existentialism.